Workshop on effective searching of online information resources - Hansen, H.H. (International Livestock Research Institute, 2007)
This power point presentation Reports the results of a workshop on scientific information for agricultural Development. It starts by looking at multistage process, then it outlines the agenda of the workshop that includes - Where and how to search; Exercises; and Reference management. Topics of discussion include - What is reference database? Why do we need it? Why do we need scientific information? Then it examines comprehensive scientific reference databases - knowing the shops and payment methods; the art and science of searching - Boolean mathematics; databases/shops; database searching; finding all names for a term (synonyms); the necessity of words; learn truncation; field limitation - using limiters to concentrate the search- title and keywords; how to use (and re-use) the literature list; reference management; and RefWorks steps for reference management. It ends with exercise, four different exercises for the four groups.